Code Mixing dalam Novel Negeri Lima Menara - Sofyaningrum, Rosita; Zuhdi, Rasyid; Cholifah, Nurul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Language is not only a set of languages, but also serves a social function. Sapir in Lyons (1982: 3) says that language is used by humans to communicate, express emotions and desires through various symbols. While Wardhaugh added that language is an arbitrary system which basically has a function as a tool for communicating. This study aims to determine code mixing in the novel language. This type of research method used is qualitative research. The method used is descriptive method, which is a research method that describes data starting from the data collection stage, data compilation, accompanied by data analysis and interpretation. In this study, the type of data analyzed using written data. The data source in this study is a novel entitled Negeri Lima Menara by A. Fuadi. Data was collected by examining data from data sources using the basic method of observation, namely by observing the form of code mixing contained in the novel in the form of sentences and followed by the method of recording data from previously observed data. Then the researcher analyzes the form of code mixing contained in the novel and concludes the results obtained. Based on the results of the analysis of the collected data, it was concluded that the incident of mixing the Minang language code into Indonesian, Javanese into Surabaya dialect into Indonesian, Sundanese into Indonesian, Arabic into Indonesian, and English into Indonesian. The sociolinguistic meaning contained in the Negeri Lima Menara novel is the meaning of intimacy and is related to kinship culture in communicating in a multilingual society which is often used in communicating within family, friends, and Islamic boarding schools. Keywords: language, code mixing , negeri lima menara